Low-dose methotrexate: not the hepatotoxic medication we once thought - Turner, Lucy Victoria Burgess (2023)
Methotrexate is a highly efficacious and frequently utilised disease-modifying medication. Concern regarding methotrexate-related hepatotoxicity has impeded the widespread application of the drug, despite a lack of high-quality evidence demonstrating a causal relationship. Methotrexate monitoring guidelines differ across various specialities. A single centre audit (n=150) demonstrated monitoring guidelines are not adhered to in over 2/3rds of patients evaluated, and hepatological concern was a significant cause of methotrexate cessation. Risk factors for alternative causes of liver disease such as Non-alcoholic fatty liver disease were commonplace, and alcohol intake was poorly documented. A large cross-sectional study of 600 individuals attending outpatient rheumatology and dermatology secondary care demonstrated a prevalence of liver fibrosis of 17.5%. There was no significant difference in prevalence between those taking methotrexate, and those who had never been exposed to it. Markers of adiposity; body mass index, waist circumference and fat mass were associated with an elevated FibroScan score. Multiple linear regression demonstrated neither methotrexate prescription nor cumulative dose of methotrexate were significant predictors of liver fibrosis. To our knowledge, this is the largest cohort study evaluating methotrexate use with liver fibrosis. There was no demonstrable relationship between the two. Although at odds with historically published reports, our findings are in keeping with the contemporaneous evidence. It seems likely that hepatotoxicity related to non-alcoholic fatty liver disease was incorrectly attributed to methotrexate. A survey of 300 patients taking methotrexate reinforced the positive effect it had had on individuals’ lives; 41% of respondents citing it’s advantageous consequences. Four in ten participants reported concerns regarding potential side-effects of methotrexate, demonstrating an apprehension about potential consequences, including hepatotoxicity. This survey suggests that the out-dated concerns relating to methotrexate-related hepatotoxicity are still negatively impacting patients to this day.
Keywords: Medicine